Efektivitas COX-2 Inhibitor Sebagai Preemptive Analgesia pada Operasi Total Knee Arthoplasty - Siriwa, Sultan Yosua; Suparto, Suparto; Ciulianto, Rudy (Universitas Kristen Krida Wacana, 2024)
Post-operative pain, especially TKA procedures, is a problem that is often encountered. The use of adequate analgesics is the main treatment to reduce the side effects of pain, namely immobilization, decreased range of motion (ROM), increased risk of thromboembolism and decreased success rate of rehabilitation. Several previous studies reported the possibility of a significant therapeutic effect on the postoperative pain response by using preemptive analgesia methods with cyclooxygenase-2 inhibitors (COX-2 inhibitors). The aim of this study was to determine the effectiveness of COX-2 inhibitors using the preemptive analgesia method in total knee arthroplasty surgery through a literature study. Data searches were carried out on several electronic journal databases PubMed, ProQuest and Google Scholar, with the keywords